2009
DOI: 10.1111/j.1365-313x.2009.04000.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics reveals the overlapping roles of hydrogen peroxide and nitric oxide in the acclimation of citrus plants to salinity

Abstract: SUMMARYHydrogen peroxide (H 2 O 2 ) and nitric oxide (·NO) are key reactive species in signal transduction pathways leading to activation of plant defense against biotic or abiotic stress. Here, we investigated the effect of pretreating citrus plants (Citrus aurantium L.) with either of these two molecules on plant acclimation to salinity and show that both pre-treatments strongly reduced the detrimental phenotypical and physiological effects accompanying this stress. A proteomic analysis disclosed 85 leaf pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
283
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(302 citation statements)
references
References 75 publications
11
283
0
8
Order By: Relevance
“…Similar to NO role in antioxidant activity in response to drought, some studies support the same NO role during the salinity tolerance. In this regard, [99] showed that exogenous NO application induce antioxidant enzymes activity, promote the maintenance of the cellular redox homeostasis and mitigate the oxidative damage produced by salt stress. Moreover, there is some experimental evidence that pre-exposure to NO efficiently protect plants to salinity.…”
Section: Effect Of No On Plant Growth Responses Under Drought and Salmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to NO role in antioxidant activity in response to drought, some studies support the same NO role during the salinity tolerance. In this regard, [99] showed that exogenous NO application induce antioxidant enzymes activity, promote the maintenance of the cellular redox homeostasis and mitigate the oxidative damage produced by salt stress. Moreover, there is some experimental evidence that pre-exposure to NO efficiently protect plants to salinity.…”
Section: Effect Of No On Plant Growth Responses Under Drought and Salmentioning
confidence: 99%
“…For example, drought-induced NO production has been reported in many plant species, including pea, wheat and tobacco [98]. Also, an increase of endogenous NO level via application of exogenous NO donor (sodium nitroprusside, SNP) has been shown to confer resistance to drought and salinity [99]. [100] reported in cucumber seedling subjected to water deficit (5 to 10 h at the stage of the third fully expanded leaf) a slight NO production in cells of root tips and in the surrounding elongation zone compared with 17 h of water deficit, which resulted in a high increase in NO production.…”
Section: Effect Of No On Plant Growth Responses Under Drought and Salmentioning
confidence: 99%
“…It has been known since the 1970s that an increase in hydrogen peroxide content affects the activity of the Calvin cycle enzymes (Kaiser 1979). Tanou et al (2009) reported that plants exposed to H 2 O 2 activated specific proteome reprogramming to prevent accumulation of proteins, e.g., the key enzymes of the Calvin cycle (Rubisco activase, Rubisco large subunit, fructose 1,6-bisphosphate aldolase, phosphoglycerate kinase, glyceraldehyde-3-phosphate dehydrogenase, phosphoribulokinase, transketolase and carbonic anhydrase). Hence, it may be speculated that the impact of rapid rehydration after drought at the tillering stage on low photosynthesis during the reproductive phase is connected with H 2 O 2 -induced gene expression related to persistent limitation in CO 2 assimilation.…”
Section: (D)mentioning
confidence: 99%
“…H 2 O 2 plays a dual role in plants: at low concentrations, it serves as a signal molecule, playing a pivotal role in signal transduction network under various stress conditions (Tanou et al, 2009;Jiang et al, 2012;Lizárraga-Paulín et al, 2013); …”
Section: Nos and Nr Pathways Involved In Spd-induced No Synthesis In mentioning
confidence: 99%